The genus Camelobaetidius Demoulin (Ephemeroptera: Baetidae) in America: Phylogenic and biogeographic analyses - Nieto Peñalver, María Carolina (2020)
The genus Camelobaetidius is the second most diverse genus of the family Baetidae in America. Also, two other genera were described as closely related to Camelobaetidius: Corinnella, and Tapajobaetis. A peculiar spatulate tarsal claw is the character shared among them. We used TNT (Tree analysis using New Technology) and GEM (Geographically explicit Event Model) to recover the phylogenic and biogeographic history of these genera. A matrix of 42 taxa and 77 morphological characters was constructed, of which 68 were treated as discrete and nonadditive (unordered), and eight as continuous. All available records of Camelobaetidius plus Corinnella, Tapajobaetis, and the species's outgroup were included in the biogeographic analysis. Corinnella and Tapajobaetis were obtained into Camelobaetidius and, therefore, are here considered junior synonyms. The founder events were the most frequent in this genus, followed by vicariance, sympatry and point sympatry. The long-distance dispersal ability in mayfly seems to be the rule instead of the exception in the history of this clade.